Dramatika brez generacije - Hrvatin, Varja (Amfiteater (Ljubljana), 2022)
In this paper, we will concentrate on the playwriting of the so-called young generation. In doing so, we will ask how this generation can be defined, given that the writers are quite individualised and dispersed among themselves, and their texts are quite diverse in terms of content, genre and form. We will argue that being born and growing up concurrently with the development of the internet, social networks and other new technologies, which are nowadays fundamentally inscribed in the social fabric, has significantly defined the young generation. Consequently, the boundaries between the virtual and the reality are constantly being blurred, and the symbiosis between the two, summed up in the term “biovirtual”, is continuously being established. Using examples of four theatre texts (The Thirty Somethings by Eva Mahkovic and Tereza Gregorič, It All Began with the Bunny Rabbit Goulash by Varja Hrvatin, The Interpretation of Sanja by Ela Božič and Work and the Maiden I-V: Serf Dramas by Nika Švab), we will reflect on how young authors are incorporating the post-internet reality, defined by the ubiquity of new technologies, into their playwriting. We will consider whether these writers’ generation generates new playwriting forms and dramaturgical approaches. Finally, we will draw attention to the conditions under which these authors operate, which (from systemic education and the repertory logic of staging to the pervasive precarisation and instability) do not provide economic security. Hence, there is no room for experiment and error. This forces writers to opt for already tested dramatic forms, strategies and themes. How, then, can one define the playwriting of a generation if it lacks a clear break with the tradition that would characterise this generation?
Keywords: biovirtual; biovirtualno; družbena omrežja; mlada generacija; new technologies; nove tehnologije; post-internet drama; postinternetna drama; Slovenian drama; slovenska dramatika; social networks; young generation